Analisis Keterampilan Berpikir Kritis Peserta Didik Kelas XII SMAN 1 Salimpaung tentang Materi Pewarisan Sifat - Femil Adella; S. Syamsurizal; Heffi Alberida; Suci Fajrina (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The 21st century requires students to have 4C skills, one of which is critical thinking skills. Learning at SMAN 1 Salimpaung is already oriented towards critical thinking skills, but it is still not optimal and the data regarding critical thinking skills is unknown. Therefore, data is needed regarding the analysis of students' critical thinking skills. This study aims to analyze the level of critical thinking skills of class XII students of SMAN 1 Salimpaung on the subject of inheritance. This research is a descriptive research. The research sample consisted of 30 students. The sampling technique used is simple random sampling. The instrument used in this study is in the form of essays on inheritance material which refers to aspects of critical thinking, Ennis (2011). The data analysis technique used is quantitative descriptive analysis. Based on the results of the research that has been done, the critical thinking skills of class XII students of SMAN 1 Salimpaung are obtained, namely the indicator of formulating questions 40% (very low), analyzing arguments 46.67% (low), considering the credibility of sources 59.17% (low), induction 21.67% (very low), deduction 41.67% (very low), make and consider decisions 20% (very low), make terms and definitions 40.83% (very low) and determine an action 24 .17% (very low) to obtain a general average of 36.53%. The conclusion of this study is that the level of critical thinking skills of class XII students of SMA Negeri 1 Salimpaung is generally still in the very low category.